STUDI KASUS PELATIHAN KERJA DAN KINERJA KARYAWAN OUTSOURCING SEKURITI DAN SOPIR PADA PT LABURA ELANG MANDIRI - Ido Hilka Zirahya; Wardoyo Wicaksono; Hanggoro Husodo; Antoni Ludfi Arifin (Cross-border, 2022)
Human resource management (HR) is an aspect that can encourage employee performance improvement. Given the importance of human resources to the development and progress of the company, the company must strive to improve the performance of its human resources to achieve company goals. Training is also a way of changing employee attitudes so that they can do their jobs more effectively. This study uses an explanatory study method (explanatory research) and is supported by written reports relating to the constraints/problems of the company's outsourcing employees. This research was conducted at PT Labura Elang Mandiri in partnership with PT Sambu Fine Chemical Koin. The results of the training and development study at PT Labura Elang Mandiri show the relationship to employee performance. Where the company has conducted training and development programs to improve company performance. The purpose of this outsourcing employee training activity is not only to have an impact on the employees being trained, but also to have an indirect impact on the company's performance.